Grand challenge in chromatin epigenomics: everything, everywhere, all at once - Dent, Sharon Y. R. (Frontiers in Epigenetics and Epigenomics, 2023)
Our understanding of the regulation and functions of histone modifications has come a long way since they were first reported in the mid-1960s. So too has our understanding of the importance of DNA methylation, histone variants, nucleosome locations and arrangements, and progressively higher order structures that impact when and where DNA-templated processes take place. Recent advances have even allowed the first ever complete sequencing and epigenomic profiles of individual chromosomes from telomere to telomere, including highly repetitive regions that were previously refractory to analysis. The regulatory power of chromatin organization for gene transcription, DNA replication, recombination and repair is undisputable. Still, an ongoing challenge is to understand the full spectrum of changes (everything) that impact processes in cells and tissues (everywhere) and how each change impacts others (all at once).